The Impact of the Postpartum “Doing-the-Month” Practice on Human Milk Microbiota: A Pilot Study in Taiwan - Po-Wen Chen; Yu-Hsien Kuo; Yi-Ling Lin (Microorganisms, 2020)
Human milk microorganisms could benefit the healthy development of the immune system in infants. In Asia, the practice of “doing-the-month” indicates a month-long period of postpartum recuperation for new mothers. This is composed of cultural practices, traditional beliefs, behavioral, dietary, and herbal therapies. In this pilot study, we evaluated the effect of “doing-the-month” on the human milk microbiota using a molecular approach. We collected two “doing-the-month” milk groups from randomly recruited mothers who had completed their “doing-the-month” program in either postpartum care center A (milk-PCA, n = 14) or postpartum care center B (milk-PCB, n = 27) for 20 to 30 days. As for the control group, milk samples were selected from postpartum mothers (milk-H, n = 46), who did not conduct the “doing-the-month” program. We found that the “doing-the-month” milk samples were associated with more diverse and unique milk microbiota and that these samples were also linked with more abundant Lactobacillus (milk-PCB) and prevalent Bifidobacteria (milk-PCA and milk-PCB). In addition, the milk samples from “doing-the-month” mothers could be enriched with more Archaea bacterial members, but the “non-doing-the-month” milk samples were enriched with more common skin-, oral-, and environmental-related bacterial members. This study highlights the impact maternal practices may have on the milk microbiome. More research is needed to investigate the effects this may have on infant immune health.